FARROWING SYNCHRONIZATION AND INDUCTION OF THE GILTS WITH PROSTAGLANDINES - RAMONA UNTARU; N. PĂCALĂ; R. MATTHIS (Scientific Papers Animal Science and Biotechnologies, 2023)
The researches were made to induce and synchronize the farrowing during the working schedule. In the trial we have been testing two hormonal products Estrumate and Prosolvin to two groups of gilts, in the 113th day of gestation. After the administration of the prostaglandin synthetic analogs we follow up the time when the gilts were farrowing, the prolificacy and the parturition loss. The percent of gilts that were farrowing during the working schedule was 48.84 at the group with Estrumate and 50.00 at the group with Prosolvin (difference non significant, χ 2 test, p>0.05). The percent of gilts that were farrowing after the working schedule 32.56 at the group with Estrumate and 16.67 at the group with Prosolvin (difference non significant, χ 2 test, p>0.05). The prolificacy was bigger for the group that were farrowing during the working schedule (10.57±0.60 pigs/gilt for the group with Estrumate and 11.43±0.12 pigs/gilt for the group with Prosolvin) comparing with the gilts that were not farrowing during the working schedule (10.21±0.79 for the group with Estrumate and 10.75±0.24 pigs/gilt for the group with Prosolvin) and significant (t test p<0.05). The parturition loss was smaller at the gilts that were farrowing during working schedule (0.67 pigs/gilt for the group with Estrumate and 0.58 pigs/gilt for the group with Prosolvin) comparing to those that were farrowing after the working schedule (1.43 pigs/gilt for the group with Estrumate and 1.20 pigs/gilt for the group with Prosolvin), but not significant statistically (t test p>0.05)